A New Implementation of Vortex Lattice Method Applied to the Hydrodynamic Performance of the Propeller-Rudder - Ghassemi, Hassan; Allafchi, Farzam (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2015)
This paper describes a new implementation of a vortex lattice method based on modified lifting line (VLML) for ship propeller-rudder. Method has been employed to estimate hydrodynamic performance and flow fields, for design and analysis. For this purpose, the results obtained using theoretical model are validated against experimental data, carried by Tamashima et al. [18], concerning to propulsor system. Comparison of these results indicates good agreement with those of the experimental data. Therefore the method can be used as a fast tool for preliminary design and analysis.